"Dreams and Deeds" and other Dualities: Nielsen and the Two-Movement Sympony - Fanning, David; Assay, Michelle (Carl Nielsen Studies, 2012)
It is well known that Nielsen’s two-movement Fifth Symphony is strongly dualistic in character. The composer himself commented that ‘A title such as “Dreams and Deeds” [Drøm og Daad] could maybe sum up the inner picture I had in front of my eyes when composing’. But it is by no means clear at what level that duality and others he mentioned are actually embodied in the work, or where it stands in relation to other two-movement symphonies composed before and after. Building on an essay by David Fanning in Carl Nielsen Studies 4, the present article fi rst considers these questions in the light of the model for symphonism proposed by the Russian scholar Mark Aranovsky. The Fifth Symphony and those two-movement symphonies found to contain the most fundamental and polarised dualities are then variously related to religious and philosophical traditions that stress dualism – from Zoroastrianism, through Yin and Yang, to Sufism, touching in passing on the philosophy of the mind and on Jung. The aim is to gain a richer and clearer picture of the uniqueness of Nielsen’s Fifth in relation both to symphonic tradition and to the history of ideas.